2017
DOI: 10.1121/1.4973690
|View full text |Cite
|
Sign up to set email alerts
|

Distraction distance and perceived disturbance by noise—An analysis of 21 open-plan offices

Abstract: Previous research suggests that, in open-plan offices, noise complaints may be related to the high intelligibility of speech. Distraction distance, which is based on the Speech Transmission Index, can be used to objectively describe the acoustic quality of open-plan offices. However, the relation between distraction distance and perceived noise disturbance has not been established in field studies. The aim of this study was to synthesize evidence from separate studies covering 21 workplaces (N = 883 respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
3
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 35 publications
3
77
3
2
Order By: Relevance
“…Further research in this field is important because a recent field study showed that noise disturbance is higher in offices where the distraction distance is large (Haapakangas et al, 2017). It was also found that the background noise level of the office (noise level of masking and ventilation) was associated with noise disturbance: the lower the background noise level was, the higher was the perceived noise disturbance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research in this field is important because a recent field study showed that noise disturbance is higher in offices where the distraction distance is large (Haapakangas et al, 2017). It was also found that the background noise level of the office (noise level of masking and ventilation) was associated with noise disturbance: the lower the background noise level was, the higher was the perceived noise disturbance.…”
Section: Methodsmentioning
confidence: 99%
“…A recent study including 21 offices provides evidence that noise disturbance is lower in offices where the distraction distance is smaller (Haapakangas et al, 2017). Distraction distance is an objective single-number quantity which describes the room acoustic quality of an open-plan office.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 5 shows the main outcomes, which are the distraction distance rD, the spatial decay rate of A-weighted speech level D2,S[dB], the A-weighted level of speech at a 4-meter distance LA,S,4m [dB] and the background noise level caused by building services, LA,B. The rD is the most essential for the perception of noise (Haapakangas et al, 2017). The rD describes how far from a single speaker the speech is distracting.…”
Section: Room Acoustic Design and Measurementsmentioning
confidence: 99%
“…Therefore, defining a space as an open-plan office is not sufficient for predicting its effects on workers. For example, the perception of office noise depends on room acoustic details which vary greatly between workplaces (e.g., Haapakangas, Hongisto, Eerola, & Kuusisto, 2017;Seddigh, Berntson, Jönsson, Danielson, & Westerlund, 2015), demonstrating the need to investigate the role of specific features within the broad category of open-plan offices.…”
Section: Introductionmentioning
confidence: 99%